2018
DOI: 10.1039/c8tc04699a
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically recyclable and self-healable conductive supramolecular polymers for customizable electronic sensors

Abstract: An intrinsically conductive supramolecular polymer is prepared with remarkable thermal sensing and recyclable ability, providing a profound potential in green electronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 44 publications
2
33
0
1
Order By: Relevance
“…Reproduced with permission: Copyright 2020, Elsevier 39 with a supramolecular crosslinked structure. 20 The recyclable ionic polymer was a co-polymerized product between an ionic conductive monomer (imidazolium acetate with vinyl group, [VEIm][Ac]) and a nonconductive monomer with quadruple hydrogen bonding motif (UHH) (Figure 5A). As well studied, the conductivities of [VEIm][Ac] and its polymerized product were both thermal sensitive, indicating the sought-for feature of producing thermometers.…”
Section: Intrinsically Conductive and Recyclable Polymermentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission: Copyright 2020, Elsevier 39 with a supramolecular crosslinked structure. 20 The recyclable ionic polymer was a co-polymerized product between an ionic conductive monomer (imidazolium acetate with vinyl group, [VEIm][Ac]) and a nonconductive monomer with quadruple hydrogen bonding motif (UHH) (Figure 5A). As well studied, the conductivities of [VEIm][Ac] and its polymerized product were both thermal sensitive, indicating the sought-for feature of producing thermometers.…”
Section: Intrinsically Conductive and Recyclable Polymermentioning
confidence: 99%
“…18,19 Without involving particular sensing materials, some cases reported that fully recyclable electronic sensors might be solely formulated by intrinsically conductive polymers. 20 From a sufficient survey, this research field is just at the emerging stage without specific review papers or progressive reports. Considering its importance and necessity, we think it is timely to present a minireview on this research frontier to summarize the recent progresses relevant to those fully recyclable electronic sensors and hopefully offer new inspirations in the electronic sensing field.…”
Section: Introductionmentioning
confidence: 99%
“…New strategies combining conductive groups (as found in polyelectrolytes) and soft groups with reversible bonds, gives both ionic conductivity and self‐healing properties. [ 67 ] This might be similar to composites in which the filler is covalently connected to the matrix or to the healable semiconductive copolymers that contain both conjugated and supramolecular (dynamic) parts. [ 68 ] Such polymers would be highly advantageous as they would eliminate the mismatch and the repulsions that exist between different phases in the composite methods.…”
Section: Self‐healing Sensing Materials and Design Strategiesmentioning
confidence: 99%
“…For example, the health conditions of human body are expected to be monitored in order to facilitate the hospital or healthcare machines to make proper actions. [84,85] To achieve this objective, sensors need to be soft enough to: 1) adapt the modulus of human tissues so as to eliminate the discomfort and 2) endure the repeated stretching and bending deformation led by the motion of joints. Soft electronic sensors based on liquid conductors are considered as an intriguing choice to satisfy these requirements that are restraining traditional sensors.…”
Section: Sensorsmentioning
confidence: 99%